2000
DOI: 10.2466/pr0.2000.86.2.389
|View full text |Cite
|
Sign up to set email alerts
|

Patients' Desire to Participate in Decision-Making in Psychiatry: A Questionnaire Survey in Japan

Abstract: Japanese national sentiment has been described as paternalistic, which has potentially wide-ranging implications for the manner in which psychiatric patients should participate in medical decision-making. To examine the extent and possible determinants of the desire to participate in medical decision-making among Japanese people, we distributed a packet of questionnaires to 747 (nonmedical) university students and 114 of their parents. The questionnaires included an imaginary case vignette of psychotic depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 5 publications
0
6
0
1
Order By: Relevance
“…Despite a lack of convincing empiric data to support the beneficial effects of information disclosure in medicine, the present literature review shows that an avenue to a better future means to disclose information to individual patients. I would like to emphasize that this is in line with the patients’ desire to know medical information related to themselves 51 . The present literature review would encourage clinicians to disclose information to patients not only from the legal aspects (patients have right to know) but also from clinical perspective (they may benefit from it).…”
Section: Discussionmentioning
confidence: 57%
“…Despite a lack of convincing empiric data to support the beneficial effects of information disclosure in medicine, the present literature review shows that an avenue to a better future means to disclose information to individual patients. I would like to emphasize that this is in line with the patients’ desire to know medical information related to themselves 51 . The present literature review would encourage clinicians to disclose information to patients not only from the legal aspects (patients have right to know) but also from clinical perspective (they may benefit from it).…”
Section: Discussionmentioning
confidence: 57%
“…The traditional mode of treatment decision‐making in Japan – the omakase (entrusting) model – is unilateral and does not promote patient education (e.g., physicians and patients seldom share disease and treatment‐related information) (11). Ultimately, this type of decision‐making limits physicians capacity to address patient ‘misperceptions’ of and resistance to psychiatric treatment (12), despite the fact that Japanese patient misperceptions of anti‐depressant medications are strongly tied to intentional non‐adherence (13).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in Japan also found education to be a determining factor. 6 About a quarter of the physicians state that they inform their patients between 50% and 90% of the time. Over half of the physicians inform their patients in general terms of their illnesses but not in detail.…”
Section: Discussionmentioning
confidence: 99%